A STUDY ON THE LOCAL GOVERNMENT'S CIVIL LIABILITY FOR FAILURE TO DISSEMINATE REGIONAL REGULATIONS IN THE GREEN ZONE - Maddenleo T. Siagian (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The Supreme Court Decision No. 3634 K/Pdt/2023 dated 22 November 2023 sets an important precedent in Indonesian civil law concerning the liability of local governments for negligence in disseminating regional zoning regulations. The case originated from a lawsuit filed by PT Wisanggeni Mitra Sejahtera against PT Bhanda Ghara Reksa, the North Jakarta City Administration, and the Financial and Development Supervisory Agency (BPKP) after the claimant’s construction project was suspended for being located within a designated green zone. The Supreme Court ruled that the defendants had committed an unlawful act (onrechtmatige daad) by failing to provide public access to zoning information as mandated by the Jakarta Regional Regulation on Spatial Planning (RTRW). This study examines the legal basis and judicial reasoning used by the Supreme Court in assessing governmental inaction as an unlawful act under Article 1365 of the Indonesian Civil Code and analyses the implications of the decision for the government’s duty to ensure transparency and accountability in spatial information disclosure. Using a normative juridical method with a case approach and library research on primary, secondary, and tertiary legal sources, this research finds that the local government’s failure to disseminate zoning information resulted in losses to private parties and violated the principle of public information transparency as regulated by Law No. 14 of 2008. The Supreme Court appropriately applied civil and administrative law principles and annulled the lower courts decisions, which had misinterpreted the elements of unlawful conduct. These ruling underscores the government’s obligation to ensure legal certainty and foster public trust in spatial governance.